Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3171/2009.4.peds08279
|View full text |Cite
|
Sign up to set email alerts
|

How long should cerebrospinal fluid cultures be held to detect shunt infections?

Abstract: Object Infections of CSF hardware may be indolent, and some patients have received antibiotic treatment for various reasons before CSF is obtained to check for a shunt infection. At present, there are few data in the literature to guide the decision as to how long to hold CSF specimens when attempting to diagnose hardware infections, and institutions vary in the duration at which cultures are considered “final.” Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…However, because bacterial meningitis has the potential to cause substantial neurological deficits, empirical antibiotic treatment is often given before CSF collection, thereby reducing its diagnostic value. Furthermore, it takes approximately 3 days for routine CSF cultures to yield results, limiting its clinical use acutely (39). Of note, fever is frequently described as a significant clinical feature of bacterial meningitis (5).…”
Section: Discussionmentioning
confidence: 99%
“…However, because bacterial meningitis has the potential to cause substantial neurological deficits, empirical antibiotic treatment is often given before CSF collection, thereby reducing its diagnostic value. Furthermore, it takes approximately 3 days for routine CSF cultures to yield results, limiting its clinical use acutely (39). Of note, fever is frequently described as a significant clinical feature of bacterial meningitis (5).…”
Section: Discussionmentioning
confidence: 99%
“…Prior antibiotic treatment is a common cause of falsely negative CSF Gram stain and culture, with up to 50% of patients having received antibiotics before CSF collection in some studies (21). Interlaboratory differences in the set up and processing of devicecollected CSF samples are another major cause of variable culture yield and performance across institutions (13,33,(42)(43)(44)(45). The recommendations regarding the need for CSF centrifugation prior to culture, anaerobic culture, anaerobic transport media, broth culture, duration of broth incubation, and the role, appropriateness, and procedure for CNS device tip cultures are frequently not explicit and differ between standard clinical microbiology references (44,45).…”
Section: Microbiologic Testingmentioning
confidence: 99%
“…Several studies have reported an increase in the proportion of positive CSF cultures and clinically significant Propionibacterium spp. infections with the addition of anaerobic culture (solid media or broth) and prolonged incubation of broth media (10 to 14 days) (13,30,42,46). Calderaro et al observed a shorter time-to-positivity and a 79% increase in the detection of aerobic bacteria and yeast with an inoculation of 1 to 3 ml CSF into a Bactec Peds Plus/F blood culture bottle over that with conventional agar culture (43).…”
Section: Microbiologic Testingmentioning
confidence: 99%
“…ve Acinetobacter spp. gibi non-fermentatif bakteriler, daha az sıklıkta olmakla birlikte, etken profi li içerisindedirler (22). Etyolojide yer alabilen bu Gram-negatif çomakların, distal ucu peritonda biten şant tiplerinde daha ön planda infeksiyon etkeni olması beklenir.…”
Section: Etyolojiunclassified